Pengaruh Sertifikasi Halal Terhadap Kinerja Umkm Kuliner Bakso Di Kabupaten Sorong - Nia Sulistiya; Rokhimah (At-Thariqah: Jurnal Ekonomi, 2024)
This study aims to analyze the extent of the influence of halal certification on the performance of meatball culinary MSMEs in Sorong Regency. This study uses a quantitative research method with a descriptive quantitative approach. The data collection techniques applied are observation, interviews and distributing questionnaires to 35 meatball culinary MSME actors with sampling techniques, namely non-probability sampling with the type of purposive sampling and data analysis techniques using a simple linear regression method. The results of the analysis show that halal certification has a positive and significant influence on the performance of meatball culinary MSMEs in Sorong Regency with a significance value of 0.46 less than 0.05 and as evidenced in the t-test with a calculated t-value of 2.070 greater than the t-value of table 1.689. The effect of halal certification on the performance of MSMEs shows a value of 11.5% while the remaining 88.5% is influenced by other factors that are not included in this study. This is because most of the meatball culinary MSME actors have not implemented halal certification, but these MSME actors are aware of the importance of halal certification.